DEVELOPMENT OF ELECTRONIC BOOKLETS-BASED COMMUNITY EDUCATION MEDIA FOR HYPERTENSION PATIENTS IN RAHAYU PUSKESMAS, BANDUNG REGENCY - Sri Indarsih; Ansori Ansori; Dewi Safitri Elshap (Journal Of Educational Experts (JEE), 2021)
The purpose of this study was to develop an Electronic Hypertension Booklet as an educational medium at the Rahayu Public Health Center, Bandung Regency and to test the feasibility of the electronic booklet that was developed, so that it could be used in the community effectively. The research method used in this study used research and development that adopting the Borg and Gall research model. The instrument used in this data collection is using a validation sheet in the form of a questionnaire and data analysis to calculate the answer score, it takes respondents, namely Hypertension Patients as the target of this research trial, as many as 40 users. And 4 people as experts. The total subjects in this study were 44 people. Digital booklet validation from the assessment questionnaire and expert validation which consists of 3 aspects, namely material, language, and design (media) aspects and all of them are very supportive The results from the assessment of experts, namely material experts, media experts and linguists are in the very category good with a percentage of 94.6%. Thus, the feasibility test of this module was carried out in two stages as follows: The first stage was the validation test of the material for the design of the booklet media, the results were very good (92.5%) stating that the electronic booklet media as an educational medium for patients was suitable for use as a learning medium. Then proceed with the second stage of testing with . With the results of expert validation and people with hypertension, the results of the development of this electronic booklet with the criteria of "very feasible".